Implementing a social prescribing program in primary care units in Portugal - Hoffmeister, Louíse Viecili (2024)
Publisher Copyright: © 2024 Hoffmeister et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.